Solitary fibrous tumor of the uterine cervix - about a case - Marinho,Márcia (2020)
Solitary fibrous tumors are rare mesenchymal neoplasms. Although first reported in the pleura, they were described at extrapeural sites, but they are uncommon in the female genital tract (less than 30 cases reported). We present a case of solitary fibrous tumor arising from uterine cervix with a benign course, as well as its histopathological and immunohistochemical features that helped establishing the diagnosis.